(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2021)
A fuel cell electric vehicle (FCEV) is an electric vehicle that uses a fuel cell to power an electric motor. FCEV aims to provide customers with the benefits of battery electric vehicles such as low-to-zero emissions, high efficiency and low maintenance, without compromising on range and recharge times. A novel power management control strategy is proposed to improve the fuel cell system simulation model that is easy to use and has acceptable accuracy at the same time. The simulation model is developed through MATLAB / Simulink software using the energy macroscopic representation method, the accuracy of this method is compared with an established model. Fuel cell integration simulation analysis is performed using experimental data from a real battery car.